ANALISIS YURIDIS BUKTI DIGITAL (DIGITAL EVIDENCE) DALAM PEMBUKTIAN PERKARA TINDAK PIDANA UJARAN KEBENCIAN PADA PUTUSAN PENGADILAN NEGERI MEDAN NO. 3168/PID.SUS/2018/PN.MDN - I Made Dwi Krisnanda, Madiasa Ablisar, Sunarmi, Mahmud Mulyadi (Res Nullius Law Journal, 2021)
Law No. 8 of 1981 concerning the Criminal Procedure Code (hereinafter referred to as the Criminal Procedure Code), has set the evidence that can be done in front of the trial. Article 183 of the Criminal Procedure Code implies that a minimum of 2 (two) valid evidence are required. Article 184 paragraph (1) of the Criminal Procedure Code regulates valid evidence, namely: witness statements; expert statements; letter; instructions; and the statement of the defendant. However, since the trial of Jesica Kumala Wongso which was broadcast on television almost every day, it turns out there is one more proof that is not contained in the Criminal Procedure Code, namely: digital evidence. The object of this study is the Medan District Court Decision No. 3168/Pid.Sus/2018/PN.Mdn., Dated May 23, 2019, concerning the use of digital evidence An. Defendant HDL Alias ​​Himma for alleged "criminal acts of hate speech". Law No. 11 of 2008 as amended by Law No. 19 of 2016 concerning Amendments to the Information and Electronic Transaction Law which governs electronic evidence. The problems in this study, namely: the position of proof of digital evidence before the trial is associated with criminal conviction; use of digital evidence in criminal acts of hate speech on social media; and juridical analysis of digital evidence in proving criminal acts of hate speech in Medan District Court Decision No. 3168/Pid.Sus/ 2018/PN.Mdn.